2021
DOI: 10.31234/osf.io/s4kr6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online Student Support: A Framework for Embedding Support Interventions into the Online Learning Cycle

Abstract: Support is one of the vital elements of online students’ success. Although many support strategies have been documented in the past, less is known at what stages of the learning cycle suggested interventions can be best embedded into the online learning curriculum. This paper aims to address this gap. First, it offers a systematic review of the empirical research on effective support interventions, as well as analyses recommendations for student support retrieved from the research on online student attrition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to Rotar (2022) the support services to be provided to DLs need to include pre enrolment advertising with comprehensive information of course, orientation program after enrolment, strong interaction system, pointing out high risk DLs and provide more care to retain them, socialization of DLs, peer mentoring and cost effectiveness policy, teaching skills, feedback and proper counselling. Arain, Khatoon & Samson (2020) conducted a research on ICT based DL system of Virtual University of Pakistan (VUP) and found students support gaps as delayed information of admissions, short help at regional level & short academic facilities at regional level.…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to Rotar (2022) the support services to be provided to DLs need to include pre enrolment advertising with comprehensive information of course, orientation program after enrolment, strong interaction system, pointing out high risk DLs and provide more care to retain them, socialization of DLs, peer mentoring and cost effectiveness policy, teaching skills, feedback and proper counselling. Arain, Khatoon & Samson (2020) conducted a research on ICT based DL system of Virtual University of Pakistan (VUP) and found students support gaps as delayed information of admissions, short help at regional level & short academic facilities at regional level.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The effectiveness of tutor-s tudent and student-student interactions is not only mediated/influenced by the various modes of communication, but also by formative assessment procedures to facilitate and support the process of e-learning (Faulconer et al, 2021;Rotar, 2022). Formative assessment constitutes an endemic aspect of well-designed online pedagogical models aimed at creating student-centred and supportive virtual learning communities.…”
Section: Formative Assessment Implementationmentioning
confidence: 99%
“…Nicol and Macfarlane-D ick (2006) discuss the ways in which students can self-evaluate and monitor their engagement with learning activities (self-generated feedback/internal feedback). Formative feedback can also help online tutors monitor students' learning with a view to providing proactive support to those students who are at risk (Rotar, 2022).…”
Section: Formative Assessment Implementationmentioning
confidence: 99%
See 1 more Smart Citation